Using theater to teach palliative care - Côté, Andréanne; Gendron-Langevin, Maud; Vachon, Mélanie; Grandmont, Danielle (Canadian Medical Education Journal, 2025)
Implication Statement Despite the benefits of palliative care, a number of myths still persist, hindering its implementation. This led to the idea of innovating how we teach through a project that aims to improve understanding of palliative care using theatrical art. This article describes the co-creation of a play and its presentation in medical and nursing courses. To assess the impact of the intervention on the level of interest and knowledge of palliative care, we used a pre- and post-performance questionnaire, the result of which suggests an improvement in these two elements. Feedback received after the event suggests that the process was enriching for both teachers and learners. Several screenings of the play are planned, for which residents of the palliative care program will be involved.